Transformation of IPAS Learning in Elementary Schools: The Strategic Role of Digital Media in Improving Students' Understanding - Sofwan Roif Ubaidillah; Arini Emha Balqis; Babul Jannah; Siti Maimuna; Mu'alimin; Erma Fatmawati (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This study aims to analyze the strategic role of digital media in enhancing students' understanding of IPAS materials and explore the challenges and strategies in its implementation. The research employed a descriptive qualitative method involving data collection through observation, interviews, and documentation. The study was conducted at SDN Kaliwates with 28 fourth-grade students as participants. The findings revealed that digital media significantly improved students' conceptual understanding by providing attractive visualizations, increasing interactivity, and offering flexible access to learning resources. Nevertheless, several challenges were identified, such as limited digital infrastructure, teachers' low digital competence, and abundant unfiltered information. To address these issues, the study suggests providing regular digital training for teachers, improving access to technological infrastructure, and curating quality digital content aligned with the curriculum. These findings underscore the importance of strategic digital integration in IPAS learning to support students' cognitive development and 21st-century skills.